Islamic Education Innovation as a Strategic Foundation in the Development of Initiator Teacher Competency : The research is to explore Islamic educational innovation as a strategic foundation in developing the competency of initiating teachers - Thoifuri, Thoifuri (TA`DIBUNA, 2025)
This research is based on the reality of Islamic education facing the challenges of globalization, digitalization, and the moral degradation of students. The aim of the research is to explore Islamic educational innovation as a strategic foundation in developing the competency of initiating teachers, not only as transmitters of material, but also as transformative agents capable of responding to change. The method used is a literature study with a descriptive qualitative approach through content analysis of relevant literature, including books, Al-Qur'an, Hadist, articles, officialy document, and previous research results. The results of the study indicate that initiating teachers have a key role in integrating the cognitive, affective, psychomotor, and spiritual dimensions of students, through creative, contextual, and Islamic-characterized learning strategies. In conclusion, Islamic educational innovation serves as a conceptual framework as well as a practice in strengthening the role of initiating teachers, thereby producing a generation that is intelligent, adaptive, religious, and civilized.